2011
DOI: 10.1021/om2002365
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Rhenium Aryl Bonds by O-Atom Transfer

Abstract: S2General Procedures: All manipulations were carried out using an argon filled MBraun glovebox and standard Schlenk techniques using over dried glassware (>1 h at 110 °C under vacuum,. THF was HPLC grade from EMD and distilled over Na/Benzophenone and then degassed under argon before use. H 2 O was degassed and stored under argon before use.Pentane was HPLC grade from EMD and distilled over NaH prior to use. Reagent-grade chemicals and solvents were purchased from Sigma Aldrich, Alfa Aesar, or EMD and used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Jaguar has been used extensively to study a wide range of homogeneous catalytic systems. Examples include Ru‐alkylidene catalysts for enyne metathesis, Ir(III) CO 2 hydrogenation catalysts, CH bond activation by Pt, Ir, and Os complexes, dioxirane‐catalyzed asymmetric epoxidations, Pd‐monophosphine catalysts for Suzuki–Miyaura coupling, Au(I) catalysts, oxy‐functionalization of ReC bonds, and Pd oxidation catalysts …”
Section: Jaguar Use In Materials Sciencementioning
confidence: 99%
“…Jaguar has been used extensively to study a wide range of homogeneous catalytic systems. Examples include Ru‐alkylidene catalysts for enyne metathesis, Ir(III) CO 2 hydrogenation catalysts, CH bond activation by Pt, Ir, and Os complexes, dioxirane‐catalyzed asymmetric epoxidations, Pd‐monophosphine catalysts for Suzuki–Miyaura coupling, Au(I) catalysts, oxy‐functionalization of ReC bonds, and Pd oxidation catalysts …”
Section: Jaguar Use In Materials Sciencementioning
confidence: 99%
“…More recently, we studied the oxidation of 2,4,6-trimethylphenylrhenium trioxide (Mes-ReO 3 , MesTO) in similar conditions. 4 We found that the lowest-barrier pathway is also through a BV type oxygen insertion, and that the replacement of alkyl by aryl migrating groups leads to an increase in the reaction rate.…”
Section: Introductionmentioning
confidence: 79%
“…Facile oxy-functionalization reactions of nucleophilic M δ+ -R δ− complexes are rare, [1][2][3][4][5] although functionalizations are well-known for M δ− -R δ+ intermediates of more electronegative metals. [6][7][8] Some of us reported recently both theory and experiments on the reaction of methylrhenium trioxide (CH 3 -ReO 3 , MTO) with oxidants (H 2 O 2 , PhIO, and IO 4 − ) in the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Developing reactivity with earlier transition metals (i.e., earlier than the Ni, Pd and Pt triad) could provide more tolerance of Lewis basic groups, but major challenges include avoiding oxidation of the metal to higher valent states that are incapable of C-H activation and developing complexes that possess electrophilic hydrocarbyl ligands (after C-H activation) [42][43][44][45][46][47][48][49][50][51][52][53]. Recently, a number of catalysts based on Ir and Rh have been shown to be active for benzene C−H activation [50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Scheme 1 Activation Of C-h Bonds By Electrophilic Substitutmentioning
confidence: 99%